Mauritania : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
This paper provides on analysis of the IMF's projections and estimates for Mauritania on gross domestic product by sector of origin at constant 1985 prices; growth of output by sector; gross domestic product and expenditures and savings at current prices; public utility rates; net production of electricity and water; civil service size and recruitment; consolidated government revenue, expenditures, and financial operations; treasury expenditure; monetary survey; balance of payments; services; assets and liabilities of the central bank and commercial banks; public investment program and its financing during 1995-99; summary of the tax systems, 2000, and so on.